Controlled Ovarian Hyperstimulation with Intrauterine Insemination Is More Successful After r-hCG Administration Than Spontaneous LH Surge - Taerk, Evan (J Reprod Infertil, 2017)
BACKGROUND: The purpose of this study was to evaluate whether clinical pregnancy rate is affected by timing intrauterine insemination (IUI) according to serum LH surge, r-hCG trigger, or a combination of LH surge and r-hCG trigger in controlled ovarian hyperstimulation (COH) cycles for patients with a variety of infertility etiologies. METHODS: The last 365 consecutive COH-IUI cycles performed at ONE Fertility Burlington in 2014 were reviewed and categorized according to method of IUI timing. Associations between categorical variables were analyzed using a combination of Chi-square and Fisher’s Exact tests, and between continuous variables using independent sample t-tests and logistic regression to a level of significance of p<0.05. RESULTS: The overall clinical pregnancy rate in this sample was 18.1% (66/365). Administration of r-hCG prior to IUI resulted in a higher clinical pregnancy rate compared with spontaneous serum LH surge: 18.2% vs. 5.8%, p=0.012. Patients in whom r-hCG was administered concomitantly with a serum LH surge had a higher clinical pregnancy than the r-hCG trigger group (30.8% vs. 18.2%, p=0.004) and LH surge group (30.8% vs. 5.8%, p<0.001). A sub-group analysis revealed that patients receiving r-FSH, rather than clomiphene or letrozole, had a significantly higher clinical pregnancy rate after r-hCG trigger as compared to the LH surge group (21.7% vs. 2.1%, p=0.01). CONCLUSION: In subfertile couples undergoing COH-IUI, r-hCG administration was associated with an increased clinical pregnancy rate compared with spontaneous serum LH surge. When r-hCG was administered concomitantly with a serum LH surge, this benefit was amplified. The effect appears to be of particular importance in r-FSH-medicated cycles.